Clinical characteristics, antimicrobial resistance, and mortality of neonatal bloodstream infections in Northern Tanzania, 2022–2023 - Ganga S. Moorthy; Matthew P. Rubach; Anna Sechu; Ronald Mbwasi; Nyemo Peter; Ibukunoluwa C. Kalu; John A. Crump; Dorothy E. Dow; Blandina T. Mmbaga; Aisa Shayo (PLoS ONE, 2025)
Neonatal bloodstream infections (BSI) make a substantial contribution to morbidity and mortality in low- and middle-income countries (LMICs), but data on the epidemiology and antimicrobial resistance (AMR) in Tanzania are limited. We describe the prevalence, resistance patterns, and associated factors of neonatal BSI at the Kilimanjaro Christian Medical Centre (KCMC), a large referral hospital in northern Tanzania. We conducted a prospective, observational study involving infants aged 0–60 days with perinatal risk factors or clinical signs of sepsis. Aerobic blood cultures were obtained at enrollment and monitored using a continuously monitored blood culture instrument. Antimicrobial susceptibility testing was performed using standard phenotypic methods. Vital status was obtained on days 2, 7, and 28 post-enrollment. BSI was defined as the isolation of established neonatal pathogens, including yeast and coagulase-negative Staphylococcus spp. (CoNS). Early-onset BSI occurred on day of life (DOL) 0-2, while late-onset BSI occurred on DOL 3 or later. Among 236 enrolled infants, blood culture was obtained in 233. BSI occurred in 106 (45.5%) of 233 infants, 50 (47.2%) were early-onset, and 56 (52.8%) were late-onset BSI. The isolated pathogens included 58 (54.7%) Gram-positive bacteria, 40 (37.7%) Gram-negative bacteria, and 8 (7.5%) yeast. CoNS (n = 55, 51.9%) and Klebsiella pneumoniae (n = 35, 33.0%) were the most common pathogens. Notably, all K. pneumoniae isolates were extended-spectrum beta-lactamase producers, resistant to ampicillin and ceftriaxone. Among the 56 infants who died, 29 (51.8%) had BSI; 11 (19.6%) infants with EO-BSI, and 18 (32.1%) with LO-BSI. Infants requiring respiratory support at admission had a 1.89-fold increased adjusted odds of BSI (95% CI, 1.05-3.44). We found high prevalence of neonatal BSI due to bacteria with a high prevalence of AMR, and BSI was associated with high mortality. There is an urgent need for effective preventive, diagnostic, and therapeutic interventions to address BSI among hospitalized infants in northern Tanzania.